Dietary patterns and semen quality: a systematic review and meta‐analysis of observational studies. (12th October 2017) - Arab, A.; Rafie, N.; Mansourian, M.; Miraghajani, M.; Hajianfar, H.
Summary: A number of studies have examined the association between dietary patterns and semen quality, but the findings have been inconclusive. Herein, we conducted a systematic review and meta‐analysis of observational studies to assess the association between dietary patterns and semen quality. PubMed, Cochrane library, Science direct, Scopus, Google Scholar, and ISI web of science databases were searched up to August 2016 for observational studies assessing the association between common dietary patterns and sperm quality markers. Data were pooled by the generic inverse variance method with random effects and expressed as mean differences with 95% confidence intervals (CIs). Heterogeneity was assessed (Cochrane Q ‐statistic) and quantified ( I 2 ‐statistic). The Newcastle‐Ottawa Scale assessed study quality. Six eligible studies, involving 8207 participants, were included in our systematic review and meta‐analysis. The pooled mean difference of sperm concentration for the healthy dietary pattern versus unhealthy dietary pattern intake was mean difference: 0.66; 95% CI, 0.305–1.016; p < 0.001. In comparison with those who had the highest adherence to healthy dietary pattern, individuals in the lowest adherence had significantly lower level of sperm concentration. However, no significant association was seen between eating patterns and other semen quality. Healthy dietary pattern seems to be associated with elevated sperm concentration level. Further longitudinal studies are needed to clarify this relationship.